The Moderating Impact of Fomo on Adoption Intention Toward Investment Behavior Among Gen Z - Maukar, Thomas Tyrellio; Sudyasjayanti, Christina (Syntax Corporation, 2025)
Cryptocurrency, a form of digital currency, has rapidly emerged as a significant player in the global financial landscape. This study examines the adoption intentions of Gen Z in Indonesia towards cryptocurrencies and explores the moderating effect of Fear of Missing Out (FOMO) on investment behaviour. Utilising the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, this research identifies key factors influencing cryptocurrency adoption, including social influence, perceived risk, and price value. The study's findings indicate that FOMO significantly impacts Gen Z's decision-making, often leading to impulsive investments driven by the desire to capitalise on high returns. The research highlights the need for better investor education and regulation to mitigate irrational behaviour influenced by social media trends and speculation. These insights aim to assist stakeholders in understanding the dynamics of cryptocurrency adoption and developing strategies tailored to young investors in emerging markets, ultimately promoting more responsible investment practices in the volatile cryptocurrency space.